Pretreatment with IFN-α increases resistance to imatinib mesylate in patients with chronic myelocytic leukemia - Xiao Yin; Hu Hui-hua; Wang Hong-xiang; Zhu Xiao-jian; Zou Ping; Chen Zhi-chao; Zhong Zhao-dong; Li Wei-ming; You Yong (Acta Pharmacologica Sinica; Vol 33, No 7 (July 2012): Acta Pharmacologica Sinica, 2016)
Chronic myeloid leukemia (CML) is a malignant hematopoietic stem cell proliferative disease driven by BCR-ABL tyrosine kinase, the product of the Philadelphia chromosome1. Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of CML. Such molecule directed against BCR-ABL firsrt introduced into clinical practice was imatinib mesylate (IM, Gleevec/Glivec, formerly STI571), which showed excellent efficacy in terms of prolonged major molecular response (MMR) and progression-free survival2. Replacing hematopoietic stem cell transplantation, IM is currently recommended as the ﬁrst-line therapy for CML by the National Comprehensive Cancer Network (NCCN) and European Leukemia Net (ELN).